MODELS AND MECHANISM OF TECHNOLOGY TRANSFER UNDER CONDITIONS OF DIGITALIZATION OF AGRICULTURAL ECONOMY: THEORY AND METHODOLOGY - Ukolova, Nadezhda; Vasilyeva, Elena; Monakhov, Sergey; Shikhanova, Juliya; Korostelev, Vyacheslav (Revista Inclusiones, 2020)
In the article, the authors consider the theoretical and methodological aspects of technology transfer in the modern agricultural economy. The works of prominent scientists of Russian and world economic science are analyzed. The most promising models of technology transfer are considered taking into account the capabilities of information and communication technologies and the formation and development of the digital economy in agriculture. In the article, the authors associate the further development of technology transfer with the improvement of the technology transfer mechanism based on the creation of technology transfer centers, as well as the creation of scientific and technological platforms, which will reduce the time for technology transfer from the development stage to its mass use. In their article, the authors identify the main types of the organizations’ interaction in the process of technology transfer. It is concluded that the creation of effective models and the improvement of the technology transfer mechanism should help to increase the efficiency of interaction among all participants in the technology transfer and the effective development of agriculture.